Sarah Ashbaugh: capstone - Ashbaugh, Sarah, artist (Colorado State University. Libraries, 2016)
The artist's statement: The natural world is a constant source of inspiration for my work. My grandfather with the "Green Thumb" instilled in me valuable knowledge and gardening practices, which contribute to my love of plant life and nature. More recently, working in a greenhouse has rekindled those roots of my childhood and my visual exploration has become more specific. In my art, I have composed and illustrated this phenomenon of nature through the human perspective. The greenhouse provides me with different views of how humans perceive nature and the degree to which we alter it. In a capitalist society, we are driven by commodities and concepts of buying and selling goods. This platform desensitizes us to nature, making it about the aesthetic appeal of the consumer. In this environment, plant life tends to be sterile, clean, decorative, and modified for the buyers' goals. Quantity, shapes, sizes, and colors are manipulated for the sake of beauty and design in our lives, conforming nature to a standardized aesthetic. Utilizing a circular format, my pieces mimic the idea of a lens or scope, which limits the subject matter that you see. It also alludes to the circle of life, which is ironic because the plants depicted are taken out of their natural environments. I also explore contrasting elements such as the man-made versus the natural, and have experimented with perceiving nature through a scavenger's standpoint. This breaks down the lens of the human perspective and shows the utilitarian view of an animal scavenger in nature. The ways in which we construct nature are not inherently bad. Rather, there is irony in how unnatural the world has become. My effort to deconstruct our perceptions is what fuels my artwork. The awe and terror in the unpredictable qualities of nature is a reminder of the sublime in the world despite our control. No doubt, this nostalgia and curiosity for nature will continue to fuel my artwork and my love of translating it into the visual.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting